A Case Analysis of Hong Kong's High-Rise Building Construction Methods - WANG ZHIHUA , WANG ZHIHUA; DR. AIMAN AL-ODAINI , DR. AIMAN AL-ODAINI; DR HJ ARAZI BIN IDRUS , DR HJ ARAZI BIN IDRUS (International Journal of Multidisciplinary Research and Studies, 2024)
Exotic "According to Anthony et al., structural systems and construction materials are just as scarce in Japan as they are in the United States (1992). In most cases, we can identify or refine the materials and methods used by our Japanese counterparts. Even in Hong Kong, incidents of a similar nature happened. The number is little "tools at one's disposal. As I oannou and "colleagues (1993) point out, rising building costs are a major concern for the American economy. High construction prices have weakened the construction industry's competitive position, leading to lower capital expenditure and an increase in manufacturing. As a result, many initiatives have been put on hold or abandoned due to a lack of funding. In the design and construction integration process, it is an important factor (Vanegas 1987), and its wise deployment has a direct impact on the efficacy of the final product (Halpin 1989). When it comes to saving money, "owners and contractors in Hong Kong are increasingly resorting to new technology. For instance, rather than building from the bottom up, employ a top-down strategy. The use of" high-strength concrete minimizes the size of the column/wall.